Diplomatiska försök att lösa den israeliska och palestinska konflikten - En jämförelse av två fredsförhandlingar - Olsson,Elisa; Saleh,Ali (2025)
In 1947 The United Nations proposed the division of Palestine between a Jewish state and an Arab state. The Jewish community accepted but the Arab states and Palestinian Arabs did not, this led to a drawn-out and bloody conflict persisted until today. Both sides have formed religious, historical, and cultural arguments about the right to the land. Several peace attempts have occasionally occurred, but none have led to real peace. The Oslo Accords (1993) and Camp-david II (2000) are important milestones in the negotiations for peace. Using a comparative study, this research looks at how these negotiations have affected the conflict and the future of peace in the context of the ongoing conflict. The study shows that the problems of Jerusalem's status, security, borders, and refugees’ rights are the key obstacles to peace. While many leaders are well-intentioned, reaching an agreement on these prickly topics seems impossible. In conclusion, peace can never be achieved unless the lack of mutual trust and recognition of each party's identity is overcome.
Keywords: Palestina; Israel; konflikt; förhandlingar; Oslo-avtalet; Camp-David II